Discovering Collaborative Advantage: The Contributions of Goal Categories and Visual Strategy Mapping. (24th July 2016) - Bryson, John M.; Ackermann, Fran; Eden, Colin
Abstract: Collaboration can make sense when there is some sort of "collaborative advantage" to be gained, meaning organizations can achieve something together that they cannot easily achieve by themselves. However, the literature is essentially silent on how to identify collaborative advantage. This article addresses this shortcoming in the theory of collaborative advantage for public purposes by proposing a set of goal categories that may be used to help articulate collaborative advantage and introducing the use of visual strategy mapping as part of a facilitated group process to figure out what the collaborative advantage might be. Collaborative advantage, as it is normally understood, consists of shared core goals. Collaborative advantage for public purposes should take into account public values beyond shared core goals . Abstract : Related Content:Potapchuk (PAR November/December 2016)